Perkembangan Gerakan Bimbingan Konseling di Indonesia dari Masa ke Masa - Mutiatul Hakimah; Titi Sunarti; Indah Febriyanti; Ifa Elfiyanti (Lembaga Pengembangan Kinerja Dosen, 2026)
Guidance and Counseling (G&C) is an essential component of the education system that plays a significant role in supporting students’ optimal personal, social, academic, and career development. The development of Guidance and Counseling in Indonesia has progressed dynamically in response to changes in educational policies, societal demands, and students’ evolving needs. This article aims to examine the historical development of Guidance and Counseling services in Indonesia, from their initial implementation to their integration within the modern curriculum framework. The study employs a qualitative approach through a literature review, with data collected using documentation analysis of relevant books, policy documents, and academic publications. The findings indicate that Guidance and Counseling in Indonesia has experienced a significant paradigm shift, moving from a service model focused primarily on problem solving and remedial intervention toward a more comprehensive approach emphasizing development, prevention, and student empowerment. This transformation has strengthened the strategic role of Guidance and Counseling in supporting national education objectives, promoting student well-being, and fostering holistic development in line with contemporary educational goals.